2017
DOI: 10.1039/c7cp00260b
|View full text |Cite|
|
Sign up to set email alerts
|

Limestone calcination under calcium-looping conditions for CO2 capture and thermochemical energy storage in the presence of H2O: an in situ XRD analysis

Abstract: This work reports an in situ XRD analysis of whether the calcination/carbonation behavior of natural limestone (CaCO) is affected by the addition of HO to the calciner at a very low concentration under relevant Calcium-Looping (CaL) conditions for CO capture in coal fired power plants (CFPP) and Thermochemical Energy Storage (TCES) in Concentrated Solar Power plants (CSP). Previous studies have demonstrated that the presence of steam in the calciner at a high concentration yields a significant increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…The thermogravimetric apparatus employed in our study does not allow for the introduction of H 2 O due to its corrosiveness, thus we chose to use 70%CO 2 /30%air atmosphere to replicate the CO 2 concentration in the calciner. Expectedly, the presence of H 2 O would accelerate the reaction as reported in previous works[28].…”
supporting
confidence: 67%
“…The thermogravimetric apparatus employed in our study does not allow for the introduction of H 2 O due to its corrosiveness, thus we chose to use 70%CO 2 /30%air atmosphere to replicate the CO 2 concentration in the calciner. Expectedly, the presence of H 2 O would accelerate the reaction as reported in previous works[28].…”
supporting
confidence: 67%
“…Similar to He, steam was found to accelerate the calcination reaction and to lower the thermodynamic driving force for its initiation [181], [220]- [225]. Unlike He, steam does affect the physical (i.e.…”
Section: Effect Of Steam On Caomentioning
confidence: 97%
“…Unlike He, steam does affect the physical (i.e. structural and morphological) properties of the CaO formed [182], [225], [226]. Champagne et al [227], [228] observed that the CO2 uptake was improved when the subsequent carbonation was performed under dry conditions.…”
Section: Effect Of Steam On Caomentioning
confidence: 99%
“…This undesirable effect may pose a serious problem for the practical application of steam in circulating fluidised beds (CFBs) during the CaL-CSP process, since fine particles (around 10 μm) generated due to fracturing are difficult to recover with commercial cyclones. Fortunately, recent in situ XRD results based on the time evolution of the weight change and crystallite size of the sorbent material, have demonstrated that the presence of SHS at small concentrations still results in remarkably improved calcination reaction rates while the mechanical strength of the CaO formed is not significantly reduced [76]. In addition to carbonation/calcination atmospheres and operating temperatures, another relevant issue is carbonation pressure, since process simulations have shown that the thermoelectric efficiency can be promoted with an increased carbonator pressure [53].…”
Section: Weight Weight Derivative (%/Min)mentioning
confidence: 99%